The formation of crews in rowing: current practices in foreign countries - Елена Яковенко; Анастасия Коженкова (National University of Physical Education and Sport of Ukraine, 2016)
One of the most promising and important areas of selection is the formation of a team and a crew. It was shown that selection for team events in rowing has its own peculiarities. Analysis of foreign experience showed that there are a variety of methods of selecting a crew in rowing. It was found that the system of selection of a crew in each country has, on the one hand, the universal aspects, and on the other hand, specific national peculiarities. The approaches used in foreign countries for selecting a crew are defined, and the main criteria, which are the most informative and relevant, for the selection of the rowers are identified. The international and national practices of the formation of crews are examined. A new algorithm for selecting rowers to form a crew is suggested. The key points in the formation of a team specific for rowing are presented.